Molecular Phylogeny of Salmonellae: Relationships among Salmonella Species Determined from gyrA, gyrB, parC, and parE Genes - CHARIS AMARANTINI; DHIRA SATWIKA (Indonesian Society for microbiology, 2015)
Study on molecular characteristics of Salmonella from clinical isolates was done in order to find out its relationship, especially those isolated from Indonesia. Partial sequence of genes belonging to QRDR region, i.e. gyrA, gyrB, parC, and parE were employed. Specific primer pairs covering those genes are used to amplify the bacterial DNA obtained. The amplicons were then analyzed by means of sequencing, and the sequences are analysed bioinformatically to find out similarities and build phylogenetic trees. By comparing all of the phylogenetic tree from QRDR region, this study revealed gyrA as the most suitable gene for rapidly identify member of salmonellae as it gives better separation of samples being analysed. However, the use of parC is recommended as it gives a consistent and reliable value to separate member of Salmonella and other Enterobacter. Further studies are under way to include member of this group, like E. coli, and the use of full sequence of QRDR genes region to verify this report.